Peculiar characteristics of ground motions in Southern Italy: Insights from global and regional ground motion models. Issue 1 (February 2023) - Regina, Gianluca; Zimmaro, Paolo; Taroni, Matteo; Akinci, Aybige
We investigate peculiar characteristics of ground motions in Southern Italy (e.g. apparent fast anelastic attenuation and trends of event terms at different periods) using a comprehensive dataset of earthquake recordings between 1969 and 2020. By doing so, we gained insights into the relative performance of eight selected region-specific, global, and global with regional adjustment ground motion models (GMMs). Our analysis is performed using a preliminary dataset (i.e. including all ground motions recorded in the area for the selected analysis period) and an independent dataset (i.e. comprising data not used to develop the models). We analyze total residuals, event terms, within-even residuals, and residuals standardized by model standard deviations (i.e. epsilon). The latter is performed to obtain a robust comparison of GMMs with different standard deviation types and levels. These approaches are employed to ground motion characterization studies for the first time in this region. Our results show that in Southern Italy, there is an apparent anelastic attenuation of the ground motion faster than in other seismic districts. Overall, regional models capture this feature better than global models. Regional adjustments to global models better capture the observed anelastic attenuation at large distances. Using the standardized residuals analysis, we observe that all selected GMMs systematically underestimate the observed ground motion for relatively high ground motion levels and its variability at any intensity levels in the study region. These outcomes may help improving future ground motion models and related engineering applications involving such models in performance-based frameworks.